Composition and Aggregate Real Wage Growth - Daly, Mary C.; Hobijn, Bart (American Economic Review, 2017)
Aggregate real wages exhibit less procyclicality than most macroeconomic models predict. We use 35 years of Current Population Survey data to confirm that the puzzling behavior of wages largely owes to changes in the composition of the employed over the business cycle. This composition effect relates to changes in both the number and the relative wage levels of those entering and exiting. The changing gap in wages of entrants and exiters is especially important for the unemployed. A large part of this wage gap is due to differences in average Mincer residuals between entrants and exiters.